The correlation between folate and vitamine E with anaemia accident of adolescents woman in islamic boarding school - Safira Kholifatul Ummah; Hasanah Fatarizka Ali Ratibi (University of Darussalam Gontor, 2021)
Background: Adolescent girls are a group that is prone to anemia. Folate and vitamin E are micronutrients that have a role in preventing anemia. Young women in islamic modern boarding schools have less controlled intake due to favorite factors or even the density of activities so that micronutrient intake is not fulfilled. Objective: This study aims to determine the relationship between folate and vitamin E with the incidence of anemia in adolescents in modern boarding schools. Method: This study uses an observational analytic method with a case-control study design. The results of this study there was a significant correlation between folate intake and anemia (p=0.000) and there was no significant relationship between vitamin E intake and anemia (p=0.099). Conclusion: Folate was associated with the incidence of anemia and vitamin E is not associated with anemia. Although there are many other factors that cause anemia in adolescents, the fulfillment of folate and vitamin E intake is still important and must be considered.